Novel treatments for rare cancers: the U.S. orphan drug act is delivering : a cross-sectional analysis - Stockklausner, Clemens; Lampert, Anette; Hoffmann, Georg F.; Ries, Markus (The oncologist, 2016)
The U.S. Orphan Drug Act of 1983 and associated incentives have fostered delivery of novel treatments for rare cancers. Quantitative cross-sectional analysis on the U.S. Food and Drug Administration Orphan Drug Product database found that more than one-third of all orphan drug approvals address needs of patients suffering from rare cancers.
Gesehen am 08.05.2019